Association between nursing work environment and compassion satisfaction among clinical nurses. (17th February 2020) - Baek, Jihyun; Cho, Hyeonmi; Han, Kihye; Lee, Haeyoung
Abstract: Aim: This study investigated the association between nursing work environment and compassion satisfaction among clinical nurses. Background: Nursing work environment and compassion satisfaction are important factors for preventing burnout and decreasing clinical nurse turnover. Method: This study used a secondary analysis and obtained data from a previous cross‐sectional study. Results: The mean scores (mean ±  SD ) for the nursing work environment and compassion satisfaction were 2.54 ± 0.34 and 33.40 ± 6.69, respectively. As the results of hierarchical regression, staffing and resources (β = 0.175, p  = .002) and collegial nurse–physician relationships (β = 0.103, p  = .038) were significantly associated with compassion satisfaction. Conclusion: Improving the nursing work environment could be an effective way to boost compassion satisfaction among nurses. Therefore, organizational support for adequate human resources and materials and mutual relations among nurses and physicians are needed. Implications for nursing management: Improvements to the work environment and the management of human resource may increase compassion satisfaction in clinical nurses.